A Spore‐Forming Probiotic Supplement Improves the Intestinal Immune Response and Protects the Intestinal Health During Recurrent Clostridioides difficile Colonization in Mice. Issue 8 (4th June 2020) - Ramezani Kapourchali, Fatemeh; Glueck, Bryan; Han, Yingchun; Shapiro, David; Fulmer, Clifton G.; Cresci, Gail A. M.
Abstract: Background: Around 15%–30% of patients develop recurrent Clostridioides difficile infection (CDI) as conventional therapies disrupt protective gut microbiota. We tested if supplementation with a spore‐forming probiotic would protect intestinal health in a mouse model of recurrent CD colonization. Methods: Methods: Female CF‐1 mice were exposed to CD spores (4‐log10 colony‐forming units/10 μL) and then randomly assigned to receive either saline (CD‐S) or probiotic (CD‐PRO). Control mice received only saline (control). Following confirmation of initial CD colonization, mice were treated with vancomycin (10 days). After 5 days, mice recolonized with CD were treated again with vancomycin (10 days) and euthanized 5 days later. Fecal samples were collected at select time points for bacterial analysis. Following euthanasia, blood samples, cecum contents, and the intestine were collected for analysis. Results: Probiotic supplementation mitigated the antibiotic‐induced changes in cecum weight ( P < .001). Probiotic‐supplemented mice had increased messenger RNA expression of several immune parameters, accompanied by lower serum iron levels compared with CD‐S mice ( P < .05). Lower expressions of TNF α and calprotectin ( P ≤ .05) were observed in CD‐PRO mice compared with CD‐S. The probiotics also supported the expression of intestinal tight junction proteins, which were diminished in the proximal colon of CD‐S mice ( P < .05). Conclusion: Mice supplemented with targeted spore‐forming probiotics exhibited improved immune responses and nutrition immunity properties, which were linked with less inflammation and enhanced intestinal barrier proteins during recurrent CD colonization.